THE EFFECT OF USING THIEVES AND CSR STRATEGIES TO IMPROVE READING COMPREHENSION SKILL AT EIGHTH GRADE SMP KINGSTON SCHOOL, DELI SERDANG - Jingga, Jenny; Sinambela, Erika; Tampubolon, Sahlan (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The purpose of this study is to determine the efficacy of applying THIEVES and CSR techniques to increase reading comprehension in Kingston School grade 8 students. The researcher devised a quasi-experimental study in order to fulfil the research's goal. The participants in this study were 108 eighth-grade Kingston School students, with 36 involved in the experimental group 1 who were taught reading comprehension using the THIEVES strategy, 36 involved in the experimental group 2 who were taught reading comprehension using the CSR strategy, and the remaining 36 involved in the control group who were taught reading comprehension using the conventional strategy. A pre-test and post-test with 40 multiple-choice items were included in the data collection instrument. The results were compared and examined to determine the efficacy of the two strategies. The experimental groups 1 and 2 scored higher than the control group, according to the results of a study. THIEVES and CSR techniques are both successful in boosting reading comprehension, according to the results. The statistics also indicate that the CSR method outperforms the THIEVES technique. Keywords: reading comprehension, THIEVES Strategy, CSR Strategy